1990
DOI: 10.1136/jech.44.2.114
|View full text |Cite
|
Sign up to set email alerts
|

A case-control study of lung cancer with special reference to the effect of air pollution in Poland.

Abstract: Study objective-The aim ofthe study was to assess the affect of inhaled pollutants on lung cancer risk.Design-The study was a retrospective case-control survey of lung cancer deaths over a six year period (1980)(1981)(1982)(1983)(1984)(1985). Information on occupation, smoking habits, and residency was collected from next of kin. Classification of exposure to community air pollution was based on measured levels of total suspended particular matter and sulphur dioxide.Setting-Cases and controls had been residen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0
3

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(69 citation statements)
references
References 28 publications
1
65
0
3
Order By: Relevance
“…Several cohort and case-control studies of outdoor air pollution have been reported (Stocks and Campbell, 1955;Hammond and Horn, 1958a/b;Haenszel et al, 1962;Haenszel and Taeuber, 1964;Dean, 1966;Hitosugi, 1968;Hammond, 1972;Cederlo¨f et al, 1975;Dean et al, 1977Dean et al, , 1978Pike et al, 1979;Hammond and Garfinkel, 1980;Doll and Peto, 1981;Vena, 1982;Tenkanen et al, 1985;Brownson et al, 1987;Samet et al, 1987;Tenkanen and Teppo, 1987;Xu et al, 1989;Jedrychowski et al, 1990;Holowaty et al, 1991;Katsouyanni et al, 1991;Mills et al, 1991;Jo¨ckel et al, 1992;Dockery et al, 1993;Tenkanen, 1993;Barbone et al, 1995;Pope et al, 1995;Zaridze et al, 1995;Biggeri et al, 1996;Engholm et al, 1996;Pawlega et al, 1997;Beeson et al, 1998;Abbey et al, 1999;McDonnell et al, 2000;Nyberg et al, 2000;Hoek et al, 2002;Pope et al, 2002). Overall, the studies suggest relative risks (RRs) of up to about 1.5 for urban vs rural residence or high vs low estimated air pollution exposure.…”
Section: Cancer Risk From Outdoor Air Pollutionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several cohort and case-control studies of outdoor air pollution have been reported (Stocks and Campbell, 1955;Hammond and Horn, 1958a/b;Haenszel et al, 1962;Haenszel and Taeuber, 1964;Dean, 1966;Hitosugi, 1968;Hammond, 1972;Cederlo¨f et al, 1975;Dean et al, 1977Dean et al, , 1978Pike et al, 1979;Hammond and Garfinkel, 1980;Doll and Peto, 1981;Vena, 1982;Tenkanen et al, 1985;Brownson et al, 1987;Samet et al, 1987;Tenkanen and Teppo, 1987;Xu et al, 1989;Jedrychowski et al, 1990;Holowaty et al, 1991;Katsouyanni et al, 1991;Mills et al, 1991;Jo¨ckel et al, 1992;Dockery et al, 1993;Tenkanen, 1993;Barbone et al, 1995;Pope et al, 1995;Zaridze et al, 1995;Biggeri et al, 1996;Engholm et al, 1996;Pawlega et al, 1997;Beeson et al, 1998;Abbey et al, 1999;McDonnell et al, 2000;Nyberg et al, 2000;Hoek et al, 2002;Pope et al, 2002). Overall, the studies suggest relative risks (RRs) of up to about 1.5 for urban vs rural residence or high vs low estimated air pollution exposure.…”
Section: Cancer Risk From Outdoor Air Pollutionmentioning
confidence: 99%
“…Earlier analytical studies generally compared residence in urban areas, where the air is considered more polluted, to residence in rural areas, sometimes providing limited data on the typical levels of some pollutants in the areas studied. Other studies have attempted to address exposure to specific components of outdoor air, providing risk estimates in relation to quantitative or semiquantitative air pollution exposure assessments (Hitosugi, 1968;Vena, 1982;Brownson et al, 1987;Jedrychowski et al, 1990;Katsouyanni et al, 1991;Mills et al, 1991;Jo¨ckel et al, 1992;Dockery et al, 1993 Biggeri et al, 1996;Pawlega et al, 1997;Abbey et al, 1999) or, in some cases, to more qualitative exposure assessments (Pike et al, 1979;Xu et al, 1989). Another type of study has addressed residence in the proximity of specific sources of pollution, such as major industrial emission sources or heavy road traffic.…”
Section: Cancer Risk From Outdoor Air Pollutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung cancer in humans is also associated with exposures to a variety of other chemical agents (Sanders 1986;Williams and Sandler 2001). The RR for lung cancer for residents in urban areas of high air pollution is about 1.5 times greater than for people living in rural areas (Lave and Seskin 1970;Jedrychowski et al 1990). The BEIR VII report (NRC 2005) and radioprotection agencies have not considered the role of many posi-C. L. Sanders and B. R. Scott tive and negative confounding factors in determining risk estimates of lung cancer from exposure to ionizing radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between risk of lung cancer and proximity to certain industries, such as iron and steel foundries or chemical, petrochemical and coke oven plants [18][19][20][21]. Another study reported increased lung cancer mortality in the proximity of a combustion installation located in Asturias [22].…”
Section: Introductionmentioning
confidence: 99%